Case report: Immune profiling links neutrophil and plasmablast dysregulation to microvascular damage in post-COVID-19 Multisystem Inflammatory Syndrome in Adults (MIS-A) - Gillrie, Mark R.; Rosin, Nicole; Sinha, Sarthak; Kang, Hellen; Farias, Raquel; Nguyen, Angela; Volek, Kelsie; Mah, Jordan; Mahe, Etienne; Fritzler, Marvin J.; Yipp, Bryan G.; Biernaskie, Jeff (Frontiers in Immunology, 2023)
Despite surviving a SARS-CoV-2 infection, some individuals experience an intense post-infectious Multisystem Inflammatory Syndrome (MIS) of uncertain etiology. Children with this syndrome (MIS-C) can experience a Kawasaki-like disease, but mechanisms in adults (MIS-A) are not clearly defined. Here we utilize a deep phenotyping approach to examine immunologic responses in an individual with MIS-A. Results are contextualized to healthy, convalescent, and acute COVID-19 patients. The findings reveal systemic inflammatory changes involving novel neutrophil and B-cell subsets, autoantibodies, complement, and hypercoagulability that are linked to systemic vascular dysfunction. This deep patient profiling generates new mechanistic insight into this rare clinical entity and provides potential insight into other post-infectious syndromes.